Agreement study in clinical research step -by-step on data analysis and interpretation using SPSS - Isa, Mohamad Rodi; Mohd Azahar, Nazar Mohd Zabadi; Shahriman Teruna, Muhammad Muaz (UiTM Press, 2025)
This book introduces statistical methods for assessing agreement between measurements in medicine, epidemiology, and health sciences. It is designed for undergraduate and postgraduate students, as well as young researchers in fields such as medicine, dentistry, physiotherapy, nursing, and pharmacy, with little statistical background. The book covers numerical and categorical data analysis, emphasising proper statistical approaches for the accurate interpretation and presentation of results. Key features include statistical computation methods for clinical research, relevant formulas, SPSS hands-on guidance, simplified result tables, and guidelines for writing agreement study manuscripts.